Molecular and morphological assessment of Varanus pilbarensis (Squamata: Varanidae), with a description of a new species from the southern Pilbara, Western Australia - Maryan, Brad; Oliver, Paul M.; Fitch, Alison J.; O’connell, Morgan (Zootaxa, 2014)
Varanus pilbarensis Storr, 1980 is a specialised saxicolous varanid endemic to the Pilbara region of Western Australia. We present genetic and morphological evidence confirming the existence of a divergent southern lineage, here described as V. hamersleyensis sp. nov.. The new species differs noticeably in having a darker colouration and a reduced pattern of small whitish ocelli on the dorsal surface of the limbs only with a largely unbanded tail. By contrast, V. pilbarensis which is redescribed and restricted to the northern lineage, is paler and more boldly patterned with large greyish ocelli on the dorsal and lateral surfaces of the body and a strongly banded tail. The two species have discrete distributions centred on the Chichester and Hamersley Ranges to the north and south of the Fortescue River Basin. This pattern of intraregional genetic structuring is similar to that found in a number of other saxicolous lizard lineages from the Pilbara.